2021
DOI: 10.1002/stc.2775
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design and performance evaluation of a novel hysteretic friction tuned inerter damper for vibration control systems

Abstract: Summary This paper studies the use of a new nonlinear damper, the hysteretic friction tuned inerter damper (HFTID), for seismic control of engineering structures. The HFTID consists of a tuned inerter damper (TID) in parallel with a hysteresis spring friction element. The analytical expressions for the force and displacement transmissibility of a SDOF system with HFTID are derived via the method of harmonic balance, and the solutions are validated through numerical simulation based on the OpenSees. Parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The hysteresis spring friction element, or Jenkins contact element, consists of a spring in series with a Coulomb friction element, it is often used to model the macro slip behavior of the contact which occurs when the contact status is characterized, during a vibration period, to a local elastic deformation and a full slip of the two surfaces [ 27 ]. New types of nonlinear damperhysteretic friction tuning inertia damper (HFTID) were also proposed [28], which can significantly improve the performance of the TMD for machining chatter suppression [29 , 30 ]. Furthermore, aaxalde [31 , 32 ] investigated the complex nonlinear modal features of a 2-DOFs system with grounded dry friction, and the simulation results showed that the modal damping was dependent on the modal amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…The hysteresis spring friction element, or Jenkins contact element, consists of a spring in series with a Coulomb friction element, it is often used to model the macro slip behavior of the contact which occurs when the contact status is characterized, during a vibration period, to a local elastic deformation and a full slip of the two surfaces [ 27 ]. New types of nonlinear damperhysteretic friction tuning inertia damper (HFTID) were also proposed [28], which can significantly improve the performance of the TMD for machining chatter suppression [29 , 30 ]. Furthermore, aaxalde [31 , 32 ] investigated the complex nonlinear modal features of a 2-DOFs system with grounded dry friction, and the simulation results showed that the modal damping was dependent on the modal amplitude.…”
Section: Introductionmentioning
confidence: 99%